Depression, Anxiety and Stress among the Undergraduate Students of Pokhara Metropolitan, Nepal - Paudel, Shishir; Gautam, Himlal; Adhikari, Chiranjivi; Yadav, Dipendra Kumar (Journal of Nepal Health Research Council, 2020)
Background: The university period is taken as a risk period for the onset of several mental disorders as this period is stressful and most of the lifetime mental disorders start typically during this young age. The present study aimed to assess the prevalence and risk factors associated with depression, anxiety, and stress among undergraduates residing at Pokhara Metropolitan, Nepal. Methods: A cross-sectional study was conducted among 681 undergraduates from different academic institutions of Pokhara Metropolitan using DASS-21 to assess the level of depression, anxiety, and stress. Results: The overall prevalence of depression, anxiety, and stress among the participants was found to be 38.2%, 46.9%, and 24.1% respectively. The level of depression and stress was not associated with the academic discipline but the higher prevalence was noted among the students from the non-technical group. The major risk factors associated with depression, anxiety and stress were parental education, family history of psychiatric disorders, self-esteem, and academic performance. Conclusions: The prevalence of mental disorders is high among the undergraduates. Further assessment of these disorders targeting students from different academic disciplines is recommended. Keywords: Anxiety; depression; risk factors; stress; undergraduates